Clinical and morphological features of Osler-Weber-Randu disease with signs of visceral injury - Pedorenko , Kateryna; Kovalchuk , Olena; Hormash , Pavlo; Gresko , Mykhailo (The Ukrainian Scientific Medical Youth Journal, 2024)
Randu-Osler-Weber disease or hereditary hemorrhagic telangiectasia is an autosomal dominant disorder characterized by dilated capillaries and veins, which are usually localized on the skin and mucous membranes of the oral cavity, as well as in the respiratory, urinary and digestive tracts. The anatomical basis of the disease is damage to blood vessels with degeneration and hypoplasia of the muscle and elastic layers, resulting in focal thinning of the vessel walls with further expansion of their lumen. Violation of angiogenesis persists throughout the patient's life, and is manifested by the formation of aneurysms, telangiectasias, and arteriovenous shunts. The average life expectancy of patients with burdened heredity is 63.2 years. The peak of mortality occurs at the age of 50, which is mainly associated with acute complications of the disease. However, among people suffering from Randu-Osler-Weber disease there are also long-lived people who die at the age of 70-79 years, and the cause of death is the complication of the main disease and the addition of chronic diseases. The purpose of this article is to consider in more detail possible manifestations and complications, methods of treatment of Randu-Osler-Weber disease for timely recognition of the disease and provision of timely medical assistance. This article describes a case of an abdominal form of hereditary hemorrhagic telangiectasia in an 82-year-old patient. The results of the postmortem pathomorphological examination of damaged tissues due to Randu-Osler-Weber disease are presented. During the study of micropreparations of the mucous lip, small intestine, mesentery of the small intestine and liver, groups of vessels were found, the wall of which is thinned in places and thickened in places, in the wall of these vessels there is a decrease or complete absence of muscle and elastic fibers, only endothelium is present, surrounded by loose connective tissue, postcapillary venules expand and anastomose with arterioles. In the lumen of these falsely developed vessels, mixed thrombi are determined. An elderly patient suffered from a combined pathology: hereditary hemorrhagic telangiectasia with arterio-venous malformations in the liver, heart, mesentery, small intestine, and coronary heart disease. These processes were complicated by the development of congestive heart failure, which disturbed the hemodynamic and rheological properties of blood and contributed to the occurrence of thrombosis of arterio-venous malformations in the mesentery and the wall of the small intestine. In the following, necrosis of the loops of the small intestine occurred with the development of diffuse purulent-fibrinous peritonitis and endogenous intoxication. Patients with hereditary hemorrhagic telangiectasia have a higher risk of bleeding and neurological complications, including anemia, cerebral abscess, stroke, venous thrombosis, and heart failure, because of late diagnosis of this hereditary disease. Early diagnosis is based on clinical data and careful collection of family history. In 90% of patients under the age of 40, the diagnosis of hereditary hemorrhagic telangiectasia can be established using the Curaçao criteria. This disease brings a significant amount of suffering in everyday life for both patients and their families, and requires significant attention of a multidisciplinary team of doctors at every stage of medical care.